POTENSI MAHASISWA REGULAR BLOCK SYSTEM (RBS) UNIVERSITAS KANJURUHAN MALANG - Susilawati, R. Anastasia Endang; Wahyono, Tries Edy (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2008)
Survey conducted to obtain get situation of quadran strategy determine elegibility of increase of maximum expense lecturing of program student of Regular Block System (RBS) at institute education of University of Kanjuruhan Unlucky enlisting and active in year of akademic 2006/2007. Used variables shall be as follows: 1) psicografis, 2) social of demography and economics, 3) geografis, 4) benefit, 5) last experience, 6) physical medium, 7) expense, 8) advertisement, 9) word of mouth communication, 10) image of PTS, 11) quality of technical service, 12) quality of functional service, 13) satisfaction of student, and 14) student expectation. Technique data collecting use quesioner which consist of question closed and is open. Obtained to be data to be analysed to descriptive method and SWOT ( strengths, weaknesses, opportunities, threats). Result of survey indicate that University of Kanjuruhan unlucky reside in aggresive strategy ( strength 71.12% and opportunity 71.1%) and also strategy diversify ( strength 71.12% and threat 69.8%), hence competent to boost up the expense of maximum study equal to 19.41% made balance to with diversification of program to overcome threats faced in this time and in the future.